METHODOLOGY FOR FORMING EARLY MEDICAL LITERACY SKILLS IN PRESCHOOL CHILDREN - BEGMURODOVA , MADINA; UMIRBAYEVA , BARNO (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This thesis substantiates a methodology for developing early media literacy skills in preschool children. The study aims to design a didactic approach that fosters perception of media messages, basic differentiation, and initial elements of critical thinking. The methodology employs observation, pedagogical experimentation, age-appropriate task design, and diagnostic criteria. Scientific novelty lies in proposing an age-adapted bank of media situations and a set of assessment indicators to support systematic instruction in preschool settings.